The Influence of PAI Teachers' Pedagogical Competence in Applying Various Learning Models on Student Motivation and Learning Outcomes - Risa Wulandari; Ellisa Fitri Tanjung; Nurzannah (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
This study aims to determine the influence of the pedagogic competence of PAI teachers in applying varied learning models on student motivation and learning outcomes. The background of this research is the need for more varied learning strategies to improve student motivation and learning outcomes. This study uses a quantitative approach with a multiple regression method. The subject of the study was grade VIII students at SMPN 2 Beringin Satu Atap, with a sample of 39 students selected through the total sampling technique. Data is collected using questionnaires or questionnaires, tests, and observations. The results of the study show that varied learning models have a positive effect on student motivation and learning outcomes. This is evidenced by the Sig. (2-tailed) values of 0.096 and 0.156 which are greater than 0.05. The conclusion of this study is that the motivation and learning outcomes of students after being given the learning model vary better than before. This study has implications that the application of varied learning can be a reference for teachers in improving learning effectiveness in terms of content, strategies, methods, and teaching approaches.